Legal Position of the Surrogate as a Substitute For a Signature In a Notarial Deed - Utomo, Hatta Isnaini Wahyu (Jurnal Hukum dan Kenotariatan, 2024)
A handwritten signature on an authentic deed serves a fundamental legal function as an identifier and acknowledgment to legalize all rights and obligations outlined in the deed. According to the regulation concerning the Notary Public Functional Position (Undang-Undang Jabatan Notaris), an authentic deed must contain the signatures of all parties involved (the notary public, witnesses, and the first and second parties) as mentioned in the deed. However, this regulation can create issues when one of the parties is unable to provide a signature on the authentic deed. This research analyzes how notarial deeds are signed for people who cannot sign. This research is normative legal research using a statutory approach and a conceptual approach. The results of this study show that there are three procedures for using a Surrogate in authentic deeds First procedure: If the individual cannot read or write but has no physical disabilities (they have all their fingers and can make a signature), a fingerprint will be used as the Surrogate. This should be noted and attached to the last page of the authentic deed; Second procedure: If the individual can read and write but has issues with their fingers (due to an injury or the absence of fingers), the Surrogate can be used, but it must be accompanied by an official medical letter from a doctor or hospital. This should also be noted and attached to the last page of the authentic deed. Third procedure: If the individual has visual impairments (is blind), the Surrogate can be used, but it must be accompanied by an official medical letter from a doctor or hospital. This should be noted and attached to the last page of the authentic deed.